(untitled) (International relations and international law Journal, 2016)
The article considers with individual interpersonal relationship in the student team their content and structure of communication skills . And also, the importance and significance in the development of student’s collective personality during the study at the university . Also there were given some examples of outstanding scientists. Formation of personality in the student team is the fulfillment of the pedagogical process of the teacher which is based on the content and structure of the student team. Interpersonal relationship – a subjective influence between people, nature and objective indicator of a mutually beneficial process attempts. Interpersonal relationship is considered to be an important thing in the student team.